A study on the preference for leadership and management with personality traits and values as antecedents - Lek, Yu Zhen (2012)
The terms leadership and management have often been used interchangeably. Despite certain similarities, both terms have distinctly different origins and specific meanings. In view of this, our study aims to empirically examine the differences and establish them as distinct but related constructs. In addition, we will examine the practical usage of this by exploring the preference for leadership and managerial roles with personality and values as antecedents. A survey questionnaire to measure leadership and management preferences was developed through a pilot study. Together with established measures of personality traits and values, a web-based survey was administered to NTU students.